Специфіка розвитку туристичної сфери Китаю - Мандрик, Ірина; Гнедько, Катерина; Mandryk, Iryna; Hnedko, Kateryna (My University, 2018)
Розкрито специфічні риси розвитку туристичної сфери Китаю. Розглянуто історичні особливості розвитку туризму в Китаї. Досліджено сучасний стан розвитку туризму в країні. Проаналізовано динаміку та географічну структуру туристичних потоків. Відображено особливості в’їзного та виїзного туризму. Охарактеризовано основні види туризму в Китаї та названо найважливіші чинники, що сприяють їх розвитку. Визначено пріоритетні напрями розвитку туризму в Китаї. The article reveals the specific features of the tourism industry in China. The historical features of the development of tourism in China are considered. The present state of tourism development in the country is explored. The article analyzes the dynamics and geographic structure of tourist flows. The features of inbound and outbound tourism are revealed. The main types of tourism in China are characterized and the most important factors contributing to their development are named. The priority directions of tourism development in China are determined.
The Specifics of the Development of Tourism in China
Keywords: туризм; турист; внутрішній туризм; міжнародний туризм; туристична сфера; Китай; tourism; tourist; domestic tourism; international tourism; China